Differential cerebral activation during observation of expressive gestures and motor acts - Lotze, M.; Heymans, U.; Birbaumer, N.; Veit, R.; Erb, M.; Flor, H.; Halsband, U. (Neuropsychologia, 2006)
We compared brain activation involved in the observation of isolated right hand movements (e.g. twisting a lid), body-referred movements (e.g. brushing teeth) and expressive gestures (e.g. threatening) in 20 healthy subjects by using functional magnetic resonance imaging (fMRI). Perception-related areas in the occipital and inferior temporal lobe but also the mirror neuron system in the lateral frontal (ventral premotor cortex and BA 44) and superior parietal lobe were active during all three conditions. Observation of body-referred compared to common hand actions induced increased activity in the bilateral posterior superior temporal sulcus (STS), the left temporo-parietal lobe and left BA 45. Expressive gestures involved additional areas related to social perception (bilateral STS, temporal poles, medial prefrontal lobe), emotional processing (bilateral amygdala, bilateral ventrolateral prefrontal cortex (VLPFC), speech and language processing (Broca's and Wernicke's areas) and the pre-supplementary motor area (pre-SMA). In comparison to body-referred actions, expressive gestures evoked additional activity only in the left VLPFC (BA 47). The valence-ratings for expressive gestures correlated significantly with activation intensity in the VLPFC during expressive gesture observation. Valence-ratings for negative expressive gestures correlated with right STS-activity. Our data suggest that both, the VLPFC and the STS are coding for differential emotional valence during the observation of expressive gestures.